Perbandingan Hasil Belajar Fiqih Menggunakan Model Pembelajaran Problem Based Learning Dan Discovery Learning Di Kelas X MAN Lima Puluh Kota - Fanelawati Fanelawati; Arifmiboy Arifmiboy; Charles Charles; Fauzan Fauzan (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2023)
Understudy learning results in FIQIH class X MAN Fifty Urban communities are still low. Scientists saw from the low grades of understudies. Then from the manner in which understudies discover that is as yet deficient. The method for defeating these issues is to apply issue based learning or revelation learning models. This review means to figure out the factors that will be involved between the exploratory class 1 utilizing the issue based learning model and the trial class 2 utilizing the revelation learning model. This kind of examination is semi exploratory with a genuine trial plan. The instrument utilized was various decision regarding the matter of Fiqh upwards of 20 inquiries with material on removal and changes in resources. Taking a huge choice worth <0.05 shows a massive contrast between the underlying variable and the last factor. As well as the presence of tremendous contrasts between learning results utilizing issue based learning and revelation learning models. So it very well may be reasoned that "there is an examination of learning results in fiqh utilizing issue based learning and revelation learning models in class X MAN Fifty Urban communities."